2007
DOI: 10.1007/s11664-007-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detection of Precipitates and Oxides on CdZnTe Surfaces by Spectroscopic Ellipsometry

Abstract: We study the surface chemistry of Cd 0.96 Zn 0.04 Te(211)B by X-ray photoelectron spectroscopy and ellipsometry. We obtain first the dielectric functions of amorphous Te and Cd on Cd 0.96 Zn 0.04 Te(211)B by in situ ellipsometry after growing thin films of each material by molecular beam epitaxy. We then study their oxidation in air and show that Cd oxidizes primarily as a hydroxide whereas Te is present as TeO 2 . In neither case is the oxidation of the films complete, as a substantial amount of either metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…3 that the curve exhibits a maximum at energy around 2 keV. This indicates that the sample contains a thin surface layer of native oxides most probably a mixture of , and CdO 48 49 . The curve for the u-CdTe sample was fitted by VEPFIT 25 using a two layer model: (i) native oxide layer on the surface and (ii) CdTe bulk region.…”
Section: Resultsmentioning
confidence: 83%
“…3 that the curve exhibits a maximum at energy around 2 keV. This indicates that the sample contains a thin surface layer of native oxides most probably a mixture of , and CdO 48 49 . The curve for the u-CdTe sample was fitted by VEPFIT 25 using a two layer model: (i) native oxide layer on the surface and (ii) CdTe bulk region.…”
Section: Resultsmentioning
confidence: 83%
“…The growth of the surface oxide layer and correlation between metallic tellurium layer evaluated with ellipsometry and tellurium peak height and width in XPS was proven already by Badano et al [16]. However, a detailed insight into the dynamics and the oxide growth rate after the chemical preparation has not been published yet.…”
Section: Resultsmentioning
confidence: 99%
“…Another peak doublet related to the oxygen bound to tellurium is also visible in Figure 2, marked as ‘oxide’. Because the doublet shift is about 3.3 eV, the measurement indicates a formation of the TeO 2 layer [16, 22]. Then the sample was chemically etched and we performed the XPS experiment again within an hour after the etching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that TeO 2 and CdTeO 3 were formed in the surface of the films. [11][12][13] The composition of undoped CdZnTe film is 51?27 at-% Te, 45?16 at-% Cd and 3?57 at-% Zn Typical I-V characteristics of the undoped and Al doped CdZnTe films were shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%